2014
DOI: 10.1111/php.12324
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Sonosynthesis of N‐Doped Nano TiO2 on Wool Fabric at Low Temperature: Introducing Self‐cleaning, Hydrophilicity, Antibacterial/Antifungal Properties with low Alkali Solubility, Yellowness and Cytotoxicity

Abstract: Nano nitrogen-doped titanium dioxide was rapidly prepared by hydrolysis of titanium isopropoxide at 75-80°C using in situ sonochemical synthesis by introducing ammonia. Various concentrations of titanium isopropoxide were examined to deposit nano nitrogen-doped titanium dioxide through impregnation of the wool fabric in ultrasound bath followed by curing. The antibacterial/antifungal activities of wool samples were assessed against two common pathogenic bacteria including Escherichia coli and Staphylococcus au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 41 publications
2
29
0
1
Order By: Relevance
“…These data suggest that N-TiO 2 NPs may generate ROS at levels that stimulate mitochondrial activity and increased cellular metabolism, but the cells are equipped with enough antioxidant mechanisms to protect them and preserve their viability. These data are in agreement with Behzadnia et al, 52 who demonstrated no adverse effects when fabrics treated with N-TiO 2 NPs were exposed to normal human dermal fibroblasts. Yet, the findings in the present study are also in contrast with the viability and cellular responses reported in other studies.…”
supporting
confidence: 83%
“…These data suggest that N-TiO 2 NPs may generate ROS at levels that stimulate mitochondrial activity and increased cellular metabolism, but the cells are equipped with enough antioxidant mechanisms to protect them and preserve their viability. These data are in agreement with Behzadnia et al, 52 who demonstrated no adverse effects when fabrics treated with N-TiO 2 NPs were exposed to normal human dermal fibroblasts. Yet, the findings in the present study are also in contrast with the viability and cellular responses reported in other studies.…”
supporting
confidence: 83%
“…The nano TiO 2 -coated fabrics, as well as those impregnated with doped TiO 2 , can harbor significant antibacterial (against Escherichia coli and Staphylococcus aureus ) and antifungal (against Candida albicans ) [18] activity, as well as self-cleaning properties, while having no adverse effects on human dermal fibroblasts [19,20]. …”
Section: Introductionmentioning
confidence: 99%
“…The test samples were removed from the cell cultures, and the cells were reincubated in fresh medium. After incubation for 24 h, the cell viability was determined by means of the MTT assay [25][26][27]. At least three data were averaged.…”
Section: Cytotoxicitymentioning
confidence: 99%